Early enteral nutrition with L-glutamine improves anastomotic healing in rats administered hyperthermic intraperitoneal chemotherapy with cisplatin and 5-FU - Alakuş, Hüseyin; Göksu, Mustafa; Erten, Siraç (Journal of Surgery and Medicine, 2021)
Background/Aim: One of the most significant aspects of intestinal surgery is anastomotic wound healing. After intestinal surgery, the most serious complication is gastrointestinal leakage, which is associated with a high rate of morbidity and mortality. The rate of morbidity and mortality can be reduced by increasing the mechanical resistance of the anastomosis. Glutamine improves impaired wound healing through effects on the healing process. This study investigated the effects of early enteral glutamine supplementation on colonic anastomosis healing in rats treated with hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin and fluorouracil (5-FU). Methods: Twenty-four rats were divided into three groups. Group 1 underwent colonic anastomosis and intraabdominal hyperthermic saline administration, Group 2 underwent colonic anastomosis and HIPEC, and Group 3 underwent colonic anastomosis and HIPEC and postoperative administration of glutamine solution via an orogastric tube for 7 days. On day 7, all rats were sacrificed and anastomotic bursting pressure (ABP) was evaluated. Tissue specimens were taken to examine tissue hydroxyproline levels and histopathological changes in the anastomotic line. Results: The ABP was significantly greater in Group 2 than in Groups 1 and 3 (P=0.001 and P=0.046, respectively). The tissue hydroxyproline level was higher in Group 1 and Group 3 than in Group 2 (P=0.001 and P=0.043, respectively). The histopathological findings in Group 3 were better than those in Group 2. The histopathological findings were observed to improve in the early enteral nutrition with Glutamine group. Conclusions: The findings of this study indicate that early enteral glutamine supplementation facilitates colonic anastomosis healing following HIPEC with cisplatin and 5-FU, by increasing the ABP and tissue concentrations of hydroxyproline and decreasing the inflammatory response.